Analisis Faktor-Faktor Yang Mempengaruhi Fraud Pengadaan Barang Dan Jasa Di Pemerintahan Desa - Sari, Ni Kadek Indah Permata; Suartana, I Wayan (E-Jurnal Akuntansi, 2020)
Advancing villages can be seen from the existence of village assistance which is increased every year and followed by an appropriate governance system in accordance with regulations or laws. However, village financial management that has not been optimal causes fraud in the field of procurement of goods and services. This study aims to examine the effect of the quality of the procurement committee, procurement ethics, procurement committee compensation, procurement systems and procedures as well as the procurement environment on fraud procurement of goods and services. The research conducted in Badung . 60 people used as respondents. Data analysis techniques used multiple linear regression. The quality of the procurement committee, procurement ethics, procurement systems and procedures have  negative effect, but the compensation of the procurement committee and the procurement environment does not affect the procurement of goods and services fraud. Keywords: Ethics and Procurement Environment, Procurement Committee Compensation, Procurement Systems and Procedures, Fraud.